Effects of Nasal Continuous Positive Airway Pressure and High-Flow Nasal Cannula on Sucking, Swallowing, and Breathing during Bottle-Feeding in Lambs - Samson, Nathalie; Nadeau, Charlène; Vincent, Laurence; Cantin, Danny; Praud, Jean-Paul (Frontiers in Pediatrics, 2018)
The use of prolonged respiratory support under the form of high-flow nasal cannula (HFNC) or nasal continuous positive airway pressure (nCPAP) is frequent in newborn infants. Introduction of oral feeding under such nasal respiratory support is however highly controversial among neonatologists, due to the fear that it could disrupt sucking, swallowing and breathing coordination and in turn induce cardiorespiratory events. The recent observation of tracheal aspirations during bottle-feeding in preterm infants under nCPAP justifies the use of animal models to perform more comprehensive physiological studies on the subject, in order to gain further insights for clinical studies. The objective of this study was to assess and compare the impact of HFNC and nCPAP on bottle-feeding in newborn lambs, in terms of bottle-feeding efficiency and safety as well as sucking-swallowing-breathing coordination. Eight full-term lambs were instrumented to record sucking, swallowing and respiration as well as ECG and oxygenation. Lambs were bottle-fed in a standardized manner during three randomly ordered conditions, namely nCPAP 6 cmH2O, HFNC 7 L/min and no respiratory support. Results revealed that nCPAP decreased feeding duration (25 vs. 31 s (control) vs. 57 s (HFNC), p = 0.03) and increased the rate of milk transfer (2.4 vs. 1.9 ml/s (control) vs.1.1 ml/s (HFNC), p = 0.03). No other indices of bottle-feeding safety or sucking-swallowing-breathing coordination were significantly altered by HFNC or nCPAP. In conclusion, our results obtained in full-term newborn lambs suggest that: i) nCPAP 6 cmH2O, but not HFNC 7 L/min, increases bottle-feeding efficiency; ii) bottle-feeding is safe under nasal CPAP 6 cmH2O and HFNC 7 L/min, with no significant alteration in sucking-swallowing-breathing coordination. The present informative and reassuring data in full-term healthy lambs must be complemented by similar studies in preterm lambs, including with mild-to-moderate respiratory distress alleviated by respiratory support in order to mimic preterm infants with bronchopulmonary dysplasia and pave the way for clinical studies.